2009
DOI: 10.1146/annurev.immunol.25.022106.141627
|View full text |Cite
|
Sign up to set email alerts
|

Horror Autoinflammaticus: The Molecular Pathophysiology of Autoinflammatory Disease

Abstract: The autoinflammatory diseases are characterized by seemingly unprovoked episodes of inflammation, without high-titer autoantibodies or antigen-specific T cells. The concept was proposed ten years ago with the identification of the genes underlying hereditary periodic fever syndromes. This nosology has taken root because of the dramatic advances in our knowledge of the genetic basis of both mendelian and complex autoinflammatory diseases, and with the recognition that these illnesses derive from genetic variant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
753
1
51

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 983 publications
(813 citation statements)
references
References 250 publications
(310 reference statements)
8
753
1
51
Order By: Relevance
“…Regarding the clinical characteristics of children, table (3,4) summarized that as it revealed highly significant difference between the studied subtypes as regards the intermittent fever (p=<0.0001), skin rash (p=<0.0001), lymphadenopathy (p=0.008), hepatosplenomegaly (p=0.008) and cardiac involvement (valve damage or pericardial effusion) (p=0.001) to systemic onset JIA rather than the other subtypes. While, the results showed no statistically significant differences regarding morning stiffness, pallor, uveitis, pleuritic, renal, skin, GIT involvements, oral and CNS disease between the three studied subtypes.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Regarding the clinical characteristics of children, table (3,4) summarized that as it revealed highly significant difference between the studied subtypes as regards the intermittent fever (p=<0.0001), skin rash (p=<0.0001), lymphadenopathy (p=0.008), hepatosplenomegaly (p=0.008) and cardiac involvement (valve damage or pericardial effusion) (p=0.001) to systemic onset JIA rather than the other subtypes. While, the results showed no statistically significant differences regarding morning stiffness, pallor, uveitis, pleuritic, renal, skin, GIT involvements, oral and CNS disease between the three studied subtypes.…”
Section: Resultsmentioning
confidence: 93%
“…1,2 It is thought to have both genetic and environmental components, triggering inflammation through immune-dysregulation which is associated with alterations in both humoral and cell mediated immunity. T lymphocytes have a central role, releasing pro-inflammatory cytokines (e.g., TNF-α, IL-6, and IL-1) 4,5 . It has heterogeneous presentation therefore, the International League of Associations for Rheumatology (ILAR) proposed different classification.…”
Section: Introductionmentioning
confidence: 99%
“…Advances defining the molecular pathology of autoinflammatory conditions have illuminated how many inflammatory diseases are driven by genetic mutations affecting elements of the innate immune system. 46 For example, in Blau syndrome, there is a gain-of-function mutations in the NOD2 gene driving nuclear factor κB transcriptional activation 47 and give rise to early onset inflammatory disease and in the skin there is an abundance of CD4 + T cells, CD68 + macrophages, and extensive expression of IFN-γ, IL-17, and IL-6. 48 Uveitic conditions express changes in inflammasome activation, including Behcet's and spondyloarthropathies.…”
Section: Understanding Uveitismentioning
confidence: 99%
“…[70][71][72] Genetic studies of CAPS identified more than 90 disease-associated genetic variants of the NLRP3 gene, the majority of which are autosomal dominant missense point mutations located in exon 3, encoding the NATCH domain ( Figure 3 and Table 1). 73,74 Despite the familial recurrence, some genetic variants inducing CAPS phenotypes result from de novo mutations. Interestingly, identical de novo mutations were independently found in different patients and often overlapped with hereditary mutations, suggesting the presence of hot-spot loci within the NLRP3 gene that exhibit high mutation susceptibility.…”
Section: Genetics Of Inflammasomes In Autoinflammatory Diseasesmentioning
confidence: 99%